Cuatro injusticias epistémicas en los currículos universitarios de filosofía en Colombia: anglo-eurocentrismo, racismo, sexismo y humanismo (2022)
It is proposed that current university philosophy curricula are based on curricular structures that would entail various forms of epistemic injustices, namely: (1) Anglo-Eurocentrism, (2) racism, (3) sexism and (4) humanism. Based on this premise, which is considered to be inscribed in the historical trajectory of Western epistemicides, the need for the decolonization of the university philosophy curriculum in Colombian universities is suggested. It is proposed as an urgent project of educational action that, immediately, would contribute to counteract the diverse forms of epistemic injustices and, transitively, would promote the materialization of what is here called curricular justice. This would not only be beneficial for the improvement and transformation of philosophy curricula at the higher education level and the gradual epistemological enrichment of philosophy, but would also contribute to a healthy recognition of pluridiversity in the university.